A profile of rare bloods in India and its impact in blood transfusion service - Sanmukh R Joshi; K Vasantha (Asian Journal of Transfusion Science, 2012)
From transfusion point of view, a rare blood is the one which lacks a high-frequency antigen as well as the one who lacks multiple common antigens and such blood donations help in transfusion to those recipients having alloantibodies to corresponding antigens. In India, we have about four such kinds of phenotypes potential enough to pose problems in providing blood to the recipients having these phenotypes. Besides, there are other four kinds of rare bloods that pose seldom problems in blood supply, though some of these may cause problems in interpretation of results on assigning proper blood groups for a person.